Variation of Woman’s Knowledge Power in the Fulfillment of Family Food Based on Economic and Social Status Difference - Yunindyawati, Yunindyawati (KOMUNITAS: International Journal of Indonesian Society and Culture, 2016)
The aim of this research is to analyze the variation of woman’s knowledge power in the fulfillment of family food based on the difference of economic and social status. The study was carried out in Ogan Ilir regency, South Sumatera Indonesia. The method of this research is qualitative method by using critical paradigm. Data were collected by in depth interview, observation and group discussion. The result of this research shows that in terms of power knowledge relation, women of high social and economic status family were subordinated by men. Women’s knowledge power in the middle social and economic status family is more dominant than man’s knowledge and power. The power relation of woman’s knowledge in the lower economic and social status is inclined to be equal to man’s knowledge power in every aspects of the fulfillment of family’s food.